The Orphan of Zhao and other Yuan plays : the earliest known versions - West, Stephen H.; Idema, W. L. (Wilt L.) (Translations from the Asian classics., 2015)
This is the first anthology of Yuan-dynasty zaju (miscellaneous comedies) to introduce the genre to English-speaking readers exclusively through translations of the plays' fourteenth-century editions. Almost all previous translations of Yuan-dynasty zaju are based on late-Ming regularized editions that were heavily adapted for performance at the Ming imperial court and then extensively revised in the seventeenth century for the reading pleasure of Jiangnan literati. These early editions are based on scripts for the leading actor and provide the reader with the arias, prose dialogue, and cue.